MANAJEMEN PEMERINTAHAN DALAM PENGELOLAAN PENERANGAN JALAN UMUM (PJU) OLEH DINAS PERHUBUNGAN KOTA PEKANBARU TAHUN 2020-2022 - Rahmadani, Bunga; Nasution, Hazqon Fuadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Public street lighting is a service provided by the government to support security and safety standards in driving. The aim of these traffic standards is so that transportation drivers can be more careful when driving so that they can reduce the number of accidents. The management of public street lighting is now given responsibility to the Pekanbaru City Transportation Department. The problem in this research is that the number of non-functioning public street lighting continues to increase every year and the most non-functioning public street lighting in Pekanbaru City will be in 2022. This will of course reduce the services provided by the government to the people of Pekanbaru City in terms of lighting public road. This also has an impact on the increasing number of accidents caused by the lack of public road lighting in Pekanbaru City. In addition, there are many complaints from the public regarding the lack of public street lighting in Pekanbaru City, which requires the Pekanbaru City government to immediately improve management of public street lighting. This research aims to describe and find out how government management is in managing public street lighting by the Pekanbaru City Transportation Department in 2020-2022. The research method used is a qualitative method by explaining descriptively. The type of data used is primary data in the form of data obtained from research informants as well as secondary data obtained from related documents that can support data for research. The research location is the Pekanbaru City Transportation Department. The research results show that government management of public street lighting is still hampered by government planning that has not been targeted and scheduled, organizing government resources that have not met needs, and using government resources that have not been implemented optimally due to a lack of communication and coordination between the government and the community. as well as government controls that have not been responded to properly by the Pekanbaru City Transportation Service. Keywords: Public Street Lighting, Government Management, Management.